Gender, occupation, and promotion to management in the nonprofit sector: the critical case of Médecins Sans Frontières Holland - Damman, M; Heyse, L; Mills, M (Wiley, 2014)
Although one can assume the work values within nonprofit organizations promote gender equality in promotion decisions, there is preliminary evidence that in the nonprofit sector women are underrepresented in higher management positions. Whereas the mechanisms resulting in underrepresentation of women in management have been studied extensively in for-profit organizations, little is known about these mechanisms in nonprofit organizations. Is gender in nonprofit organizations—even given the underlying values of these organizations—an impediment to attaining a management position? This article presents a case study of employment patterns within the Dutch section of the humanitarian INGO Médecins Sans Frontières and focuses particularly on the effects of gender and occupation on transitions to management. The case study organization represents a “critical case” because the nature of this organization's work environment can be expected to result in a relatively high percentage of women in management. Employee records (N = 2,247) were analyzed using event history models. We found that women made the transition to management less rapidly than men, even when controlling for factors like age, previous work experience, and nationality. However, gender differences were completely explained by occupation. Those employees in female-dominated occupations (in this case, medical personnel such as nurses) had a lower promotion-to-management rate than those in male-dominated occupations (in this case, nonmedical personnel such as financial officers), irrespective of their gender. This case study highlights the importance to nonprofit management research of studying the effects of occupational sex segregation on promotion.